Gastric metaplasia of the duodenal mucosa in Crohn’s disease: novel histological and endoscopic findings - Ikezono, Go; Yao, Kenshi; Imamura, Kentaro; Kanemitsu, Takao; Miyaoka, Masaki; Hirano, Akikazu; Takeda, Kazuhiro; Hisabe, Takashi; Ueki, Toshiharu; Tanabe, Hiroshi; Ota, Atsuko; Haraoka, Seiji; Iwashita, Akinori (Endoscopy International Open, 2021)
Background and study aims Upper gastrointestinal endoscopy and biopsy are useful for differential diagnosis of Crohn’s disease (CD) of the large intestine and ulcerative colitis (UC). We aimed to identify novel histopathological and endoscopic findings in the upper gastrointestinal tract in patients with CD who did not have Helicobacter pylori infection.Patients and methods Upper gastrointestinal endoscopy was performed on patients with CD and UC. Mucosal lesions detected were subsequently observed using magnifying endoscopy with narrow-band imaging (M-NBI), following which biopsy was performed. When no mucosal lesion was detected on conventional endoscopy, M-NBI and biopsy were performed on four sites: the gastric body, gastric antrum, duodenal bulb, and second portion of the duodenum.Results The prevalences of gastric metaplasia (GM) were 48 % (24/50) and 16 % (8/50) in the CD and UC groups, showing a significant difference (P = 0.001). In 23 of 24 patients with histologically proven GM in the CD group, mucosal lesions were detected using conventional white-light imaging (C-WLI). In 22 of 24 patients with histologically proven GM in the CD group, disappearance of normal villous structure and the presence of curved marginal crypt epithelium were noted using magnifying endoscopic findings characteristic of GM (M-GM). A combination of C-WLI and M-NBI yielded a significantly increased specificity (P = 0.004) and accuracy (P = 0.039).Conclusions The prevalence of GM in the duodenal mucosa was significantly higher in patients with CD than in controls. The identified endoscopic findings may be useful as novel indicators for the histological diagnosis of GM in the duodenum.